Auto-Mapping and Configuration Method of IEC 61850 Information Model Based on OPC UA - In-Jae Shin; Byung-Kwen Song; Doo-Seop Eom (Energies, 2016)
The open-platform communication (OPC) unified architecture (UA) (IEC62541) is introduced as a key technology for realizing a variety of smart grid (SG) use cases enabling relevant automation and control tasks. The OPC UA can expand interoperability between power systems. The top-level SG management platform needs independent middleware to transparently manage the power information technology (IT) systems, including the IEC 61850. To expand interoperability between the power system for a large number of stakeholders and various standards, this paper focuses on the IEC 61850 for the digital substation. In this paper, we propose the interconnection method to integrate communication with OPC UA and convert OPC UA AddressSpace using system configuration description language (SCL) of IEC 61850. We implemented the mapping process for the verification of the interconnection method. The interconnection method in this paper can expand interoperability between power systems for OPC UA integration for various data structures in the smart grid.